2020
DOI: 10.1111/ene.14248
|View full text |Cite
|
Sign up to set email alerts
|

EAN guideline on palliative care of people with severe, progressive multiple sclerosis

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 62 publications
(130 reference statements)
0
32
0
2
Order By: Relevance
“…Relevance is critical for ACP. Although Solari et al [14] recently reported that as many as 89% of people with severe MS want to discuss ACP, preliminary findings from a study on ACP in MS indicate that while participants were generally positive about ACP, it was no more relevant to them than to anybody, regardless of their MS diagnosis. Concerning their MS specifically, participants were reluctant to engage in ACP because of the uncertainty of their disease trajectory [15].…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Relevance is critical for ACP. Although Solari et al [14] recently reported that as many as 89% of people with severe MS want to discuss ACP, preliminary findings from a study on ACP in MS indicate that while participants were generally positive about ACP, it was no more relevant to them than to anybody, regardless of their MS diagnosis. Concerning their MS specifically, participants were reluctant to engage in ACP because of the uncertainty of their disease trajectory [15].…”
Section: Discussionmentioning
confidence: 85%
“…platform on which more accurate and realistic prognostic information can be shared with people with MS; this is essential to help them make sense of their illness and reframe their selfimage. Recent European Academy of Neurology (EAN) guidelines for palliative care in MS include early discussion of disease progression and future planning with people with severe MS [14]. Realistic hope is also important; our findings indicate health professionals do not discuss ACP for fear of distressing people with MS.…”
Section: Plos Onementioning
confidence: 83%
See 1 more Smart Citation
“…Ten clinical questions were formulated. 9,10 They encompassed general and specialist palliative care, advance care planning, discussion with healthcare professionals the patient’s wish to hasten death, symptom management, multidisciplinary rehabilitation, interventions for caregivers (training programs on caregiving; practical and/or emotional support programs), and interventions for healthcare professionals (MS professionals’ training in palliative care; palliative care professionals’ training in MS care).…”
mentioning
confidence: 99%
“…A total of 34 recommendations (33 weak, 1 strong) and 7 good practice statements were developed. 9,10 The provision of home-based palliative care, either general or specialist, is recommended with weak strength. 9,10 Areas that currently lack evidence of efficacy in this population include advance care planning, the management of symptoms such as fatigue and mood problems, and interventions for caregivers and healthcare professionals.…”
mentioning
confidence: 99%